Genomic Diversity of Pigeon Pea (Cajanus cajan L. Millsp.) Endosymbionts in India and Selection of Potential Strains for Use as Agricultural Inoculants - Jorrin, Beatriz; Maluk, Marta; Atoliya, Nagvanti; Kumar, Shiv Charan; Chalasani, Danteswari; Tkacz, Andrzej; Singh, Prachi; Basu, Anirban; Pullabhotla, Sarma VSRN; Kumar, Murugan; Mohanty, Santosh Ranjan; East, Alison K.; et al. (Frontiers in Plant Science, 2021)
Pigeon pea (Cajanus cajan L. Millsp.) is one of the legume crops most resilient to climate change. It is grown by millions of resource-poor farmers in semi-arid and tropical subregions of Asia and Africa, as a major contributor to their nutritional food security. Pigeon pea is the sixth most important legume in the world, with India contributing more than 70% of the total production and harbouring a wide variety of cultivars. Nevertheless, its seed yield remains low, mainly because pigeon pea suffers from poor nodulation as it is grown mainly under dryland conditions and therefore plants are often nitrogen-starved. Despite its importance in India, pigeon pea endosymbiont genomic diversity studies have only been performed in a few countries in the American and African continents, showing that the preferred endosymbionts are members of Bradyrhizobium spp.. Since such a study is particularly valuable when performed in India, we isolated pigeon pea endosymbionts from different soil types in Southern, Central and Northern India. After functional characterisation of the isolated strains, we selected 19 strains for genome sequencing along with 8 inoculants obtained from the ICRISAT culture collection. The phylogenomic analysis (ANIm) revealed the diversity of this population and their relationship with members of both the Bradyrhizobium and Ensifer genera. Based on nodC phylogeny and nod cluster synteny Bradyrhizobium yuanmingense is the most common endosymbiont, harbouring nod genes similar to those of Bradyrhizobium cajani and Bradyrhizobium zhanjiangense. Our results provide the basis for development of pigeon pea inoculants to increase the yield of this legume through use of effective nitrogen-fixing species, tailored for the different agroclimatic regions of India.